Assessment of Agricultural Information Needs in African, Caribbean and Pacific (ACP) States: Eastern Africa: Country study Mauritius - Ng Kee Kwong, R. (Technical Centre for Agricultural and Rural Cooperation, 2008)
This study aims to provide an overview of main agricultural services and actors in terms of their strengths, weaknesses and opportunities for collaboration with CTA; to identify the agricultural information and ICM capacity building needs of key strategic partners for CTA products and services; and to have an update of the status of ICM and ICTs in Mauritius.